Superação de dormência em ormosia arborea (Fabaceae: Papilionoideae) pela utilização de dois métodos de escarificação mecânica em diferentes pontos do tegumento - Basqueira, Reginaldo Augusto; Pessa, Henderson; De Souza-Leal, Thiago; Pedroso-De-Moraes, Cristiano (My University, 2011)
The dormancy state in Ormosia arborea seeds is caused by tegument impermeability. Two scarification mechanisms at different sites in the tegument are analyzed to determine the best methodology in the overcoming of dormancy and germination of the specie. Seeds were distributed in batches on four petri plates with 25 seeds each. They were previously covered with two sheets of filter paper moistured with 10 mL distilled water and taken to B.O.D climate chamber at 25°C ± 2, under a white light from 32.85 ?mol.m-2.s-1 fluorescent lamps, until their germination. Germination test results underwent ANOVA variance analysis and Turkey's test at 5% probability. Statistical analysis showed that scarification treatment with sandpaper on the medial portion of the orange-reddish lateral surface provides the best method in overcoming dormancy in Ormosia arborea seeds. The highest germinability rates and germination velocity are thus reached.
Two mechanical scarification methods at different skin sites for dormancy overcoming in Ormosia arborea (Fabaceae: Papilionoideae)
Keywords: Germination; Seeds; Tegument; Vegetal Production